Impact of Scapular Stabilization Exercises on Pain, Shoulder Position, and Volleyball Performance in Players with Scapular Dyskinesia - Roghayeh Karimi; Ebrahim Mohammad Ali Nasab Firouzjah (Shiraz University of Medical Sciences, 2024)
Background: This study aimed to examine the impact of a regimen of scapular stabilization exercises on pain, shoulder position, and performance in volleyball players diagnosed with scapular dyskinesia.Methods: This semi-experimental, applied study involved 30 female volleyball players with scapular dyskinesia, who were purposefully selected and randomly assigned to control and training groups. The position of the shoulder, shoulder pain, and specific performance of the volleyball players were assessed using photographic methods, a numeric pain rating scale, and the AAHPERD service test. The training group performed scapular stabilization exercises for eight weeks. Post-tests were conducted after the exercise regimen. Parametric data were analyzed using paired t-tests and analysis of covariance, while non-parametric data were evaluated using the Wilcoxon and Yeoman-Whitney tests.Results: The findings indicated that an eight-week program of scapular stabilization exercises significantly improved shoulder position and specific performance and reduced shoulder pain in volleyball players with scapular dyskinesia.Conclusion: Scapular stabilization exercises can effectively enhance shoulder position, improve specific performance, and alleviate shoulder pain in volleyball players suffering from scapular dyskinesia.